Research progress on causes and interventions on enteral nutrition-associated diarrhea in critically ill patients (危重症患者肠内营养相关性腹泻发生原因及干预措施的研究进展) - LIU Qing (刘晴); GU Yanmei (谷艳梅) (Association of Integrative Nursing, 2022)
The enteral nutrition-associated diarrhea is closely related to fasting time, hypoproteinemia, enteral nutrient solution, drug factors and other issues, affecting the rehabilitation of critically ill patients. This paper summarized the causes, prevention and nursing measures of enteral nutrition-associated diarrhea, in order to provide reference for improving the quality of nursing for critically ill patients. (危重症患者肠内营养相关性腹泻与禁食时间、低蛋白血症、肠内营养液、药物因素等密切相关, 腹泻会对危重症患者的康复造成影响。本文对危重症患者肠内营养相关性腹泻的发生原因、预防以及护理措施进行总结, 以期为进一步提高危重症患者肠内营养相关性腹泻的护理质量提供理论依据。)